Spatiotemporal diversity and community structure of cyanobacteria and associated bacteria in the large shallow subtropical Lake Okeechobee (Florida, United States) - Lefler, Forrest W.; Barbosa, Maximiliano; Zimba, Paul V.; Smyth, Ashley R.; Berthold, David E.; Laughinghouse, H. Dail (Frontiers in Microbiology, 2023)
Lake Okeechobee is a large eutrophic, shallow, subtropical lake in south Florida, USA. Due to decades of nutrient loading and phosphorus rich sediments, the lake is eutrophic and frequently experiences cyanobacterial harmful algal blooms (cyanoHABs). In the past, surveys of the phytoplankton community structure in the lake have been conducted by morphological studies, whereas molecular based studies have been seldom employed. With increased frequency of cyanoHABs in Lake Okeechobee (e.g., 2016 and 2018 Microcystis-dominated blooms), it is imperative to determine the diversity of cyanobacterial taxa that exist within the lake and the limnological parameters that drive bloom-forming genera. A spatiotemporal study of the lake was conducted over the course of one year to characterize the (cyano)bacterial community structure, using 16S rRNA metabarcoding, with coincident collection of limnological parameters (e.g., nutrients, water temperature, major ions), and cyanotoxins. The objectives of this study were to elucidate spatiotemporal trends of community structure, identify drivers of community structure, and This is a provisional file, not the final typeset article examine cyanobacteria-bacterial relationships within the lake. Results indicated that cyanobacterial communities within the lake were significantly different between the wet and dry season, but not between periods of nitrogen limitation and co-nutrient limitation. Throughout the year, the lake was primarily dominated by the picocyanobacterium Cyanobium. The bloom-forming genera Cuspidothrix, Dolichospermum, Microcystis, and Raphidiopsis were highly abundant throughout the lake and had disparate nutrient requirements and niches within the lake. Anatoxin-a, microcystins, and nodularins were detected throughout the lake across both seasons. There were no correlated (cyano)bacteria shared between the common bloom-forming cyanobacteria Dolichospermum, Microcystis, and Raphidiopsis. This study is the first of its kind to use molecular based methods to assess the cyanobacterial community structure within the lake. These data greatly improve our understanding of the cyanobacterial community structure within the lake and the physiochemical parameters which may drive the bloom-forming taxa within Lake Okeechobee.